Vitamina C na expressão gênica de marcadores de estresse oxidativo em fibroblastos de pacientes com queimadura - Bonucci, Jessica [UNIFESP] (2016)
Introduction: Introduction: burn injury is a complex trauma with laborious treatment, serious economic and social repercussions mainly in public health. It is among the leading causes of morbidity and mortality. The thermal injury mediates a common systemic response, regardless of the location or extent of the injury, as well as specific responses adjascent or distant to trauma. Genes related to oxidative stress were differentially expressed in groups of patients with burns. Furthermore, significant reductions in the concentration of vitamin C have been reported in patients with major burns. Several studies have demonstrated the importance of Vitamin C in major trauma victims. Objective: Evaluate the effect of Vitamin C in the expression of 84 oxidative stress genes in human fibroblasts cultured from patients with burn. Methods: Skin fragments from ten burned patients (burn group) and eight healthy patients (control group). Were treated to culture of primary human fibroblasts conduced by explant method and distributed into 4 groups: GQ + (n = 10 - Burning fibroblasts treated with Vitamin C), GQ- (n = 10 - Burning fibroblasts without treatment), GC + (n = 8 - control fibroblasts treated with Vitamin C) and GC- (n = 8 - control fibroblasts without treatment). The gene expression analysis was done by qPCR Array, making six comparisons: 1) GC + versus GC-; 2) GQ- versus GC-; 3) GQ + versus GC-; 4) GQ- vs. GC + - 5) versus CG + versus GQ + and 6) GQ+ versus GQ-. Results: Comparisons 1 and 3 showed no altered gene. Comparisons 2 and 4 showed the same sixty-five down-regulated genes. Comparison 5 had seventy-one down- regulated genes, wich 64 were equal to 2 and 4. Comparison 6 showed 10 up-regulated genes. Conclusion: Supplementation of Vitamin C in cultivated fibroblast cells from patients with burn injury showed alter the expression of ten genes related to oxidative stress, all showed hyper expressed, being those of greatest interest DUOX1, GPX5, GPX2 e PTGS1.